2018
DOI: 10.1111/pace.13369
|View full text |Cite
|
Sign up to set email alerts
|

Severe tricuspid regurgitation due to interactions with right ventricular permanent pacemaker or defibrillator leads

Abstract: Although thought to be a rare event, permanent pacemakers and implantable cardioverter-defibrillators with right ventricular intracardiac leads have the potential to induce tricuspid valve dysfunction. Adverse lead-valve interactions can take place through a variety of mechanisms including damage at the time of implantation, leaflet pinning, or long-term fibrosis encapsulating the leaflet tissue. Clinical manifestations can display a wide range of severity, as well as a highly variable time span between implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 75 publications
3
21
0
1
Order By: Relevance
“…In the present study, we also demonstrated a significant reduction of PASP with HBP and a consequent amelioration of TR severity classification after HBP. Previous studies linked the worsening of TR with RV lead implantation positioned across the tricuspid valve 30–33 . In these studies, a decline in TAPSE and S wave velocity due to RVP was mainly responsible for the worsening of TR; we confirm a significant deterioration in longitudinal systolic function in our RVP group while we found preserved TAPSE and S wave velocity between baseline and follow up in the HBP group 30–33 .…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, we also demonstrated a significant reduction of PASP with HBP and a consequent amelioration of TR severity classification after HBP. Previous studies linked the worsening of TR with RV lead implantation positioned across the tricuspid valve 30–33 . In these studies, a decline in TAPSE and S wave velocity due to RVP was mainly responsible for the worsening of TR; we confirm a significant deterioration in longitudinal systolic function in our RVP group while we found preserved TAPSE and S wave velocity between baseline and follow up in the HBP group 30–33 .…”
Section: Discussionsupporting
confidence: 80%
“…In the initial phase after implantation, there is local deposition of blood platelets and fibrin on the surface of the lead. Then fibrous capsule is formed and the process mimicking scarring begins (Candinas et al, 1999; Dundar et al, 2011; Esposito et al, 2002; Kołodzińska et al, 2012; Trankle et al,2018). Lead endothelialization is characterized by varying intensity and progresses at its own pace in individual patients, additionally the fibrous reaction varies depending on the course of the lead.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 23.5% of patients were found to have significant tricuspid regurgitation (grade III and IV), whereas significant lead‐related tricuspid dysfunction was confirmed in 6.2% of patients. In the available studies, the incidence of LDTD was estimated to range from 10% to 39% (Al‐Bawardy et al, 2015; Chang et al, 2017; Höke et al, 2014; Polewczyk et al, 2013; Trankle et al, 2018). Such discrepancies may result from difficulties in imaging the mechanism of tricuspid regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…В дальнейшем эти явления могут привести к функциональным нарушениям клапана и правых камер сердца. При этом клинические проявления могут демонстрировать широкий спектр тяжести состояния пациента, а также весьма вариабельный временной интервал между имплантацией и ухудшением гемодинамики [20].…”
Section: Discussionunclassified